Role of Inhaled Nitric Oxide in the Management of Severe Acute Respiratory Distress Syndrome - Hunt, Juliette Lucinda; Bronicki, Ronald A.; Anas, Nick (Frontiers in Pediatrics, 2016)
To date, there have been several systematic reviews with meta-analysis that have shown no reduction in mortality with the use of inhaled nitric oxide (iNO) in patients with acute respiratory distress syndrome (ARDS). Importantly, these reports fail to make a distinction between the pediatric and adult patient. The number of adult patients in these reviews are far greater than the number of pediatric patients which makes it difficult to interpret the data regarding the role of iNO on the pediatric population. Extrapolating data from the adult population to the pediatric population is complicated, as we know that physiology and the body’s response to disease can be different between adult and pediatric patients. iNO has been demonstrated to improve outcomes in term and near-term infants with hypoxic respiratory failure associated with pulmonary hypertension. Recently, Bronicki et al. published a prospective randomized control trial investigating the impact of iNO on the pediatric patient population with acute respiratory failure. In this study, a benefit of decreased duration of mechanical ventilation and an increased rate of ECMO-free survival was demonstrated in patients who were randomized to receiving iNO, suggesting that there may be benefit to the use of iNO in pediatric ARDS (PARDS) that has not been demonstrated in adults. iNO has repeatedly been shown to transiently improve oxygenation in all age groups, and yet neonates and pediatric patients have shown improvement in other outcomes that have not been seen in adults. The mechanism that explains improvement with the use of iNO in these patient populations are not well understood but does not appear to be solely a result of sustained improvement in oxygenation. There are physiologic studies that suggest alternative mechanisms for explaining the positive effects of iNO, such as platelet aggregation inhibition and reduction in systemic inflammation. Hence the role of iNO by various mechanisms and in various age groups warrants further investigation.